Between Entrepreneurship and Community Empowerment: The Management Model of Empowering Small Business’ Borneo Queen Community - Adiwijaya, Saputra; Adam, Chaidir; Rafsanjani, Muhammad Arief; Sustiyah; Simanjuntak, Atmaezer Hariara (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
The management approach of Borneo Queen Community emphasizes the pivotal role of managerial efforts in sustaining small businesses while concurrently fostering community empowerment. This study endeavors to explore the proprietor’s influence in ensuring the continuity of Borneo Queen Community and its positive impact on community advancement. Employing a qualitative methodology with a phenomenological lens, the research unveils the proprietor’s strategies in empowering the business through a distinctive worker recruitment mechanism. This approach prioritizes the betterment of the local community’s welfare, particularly targeting youth with limited educational and economic prospects. By granting them autonomy in managing and honing their skills, the business not only fosters employee development but also maintains a strong economic focus. Furthermore, the business demonstrates astute market foresight by leveraging various digital platforms for expansive marketing outreach. Through this integrated approach, Borneo Queen Community emerges as a small business entity adept at harmonizing commercial success with community empowerment.